2021
DOI: 10.1186/s13293-021-00364-5
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors in pain modulation: cellular signaling

Abstract: Sensory perception and emotional disorders are disproportionally represented in men and women and are thus thought to be modulated by different sex hormones in various conditions. Among the most important hormones perceived to affect sensory processing and transduction is estrogen. Numerous previous researchers have endeavored to demonstrate that estrogen is capable of modulating the activity of sensory neurons in peripheral and central sites in female, male, or castrated animals. However, the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 136 publications
0
35
0
2
Order By: Relevance
“…We are currently focused on identifying which nuclear and/or membrane estrogen receptors (ERα, ERβ, or GPER) are involved in potentiating the effects of 5HT on trigeminal sensory neurons. Previous studies have reported that ERα, ERβ, and GPER are present in trigeminal sensory neurons ( Chen et al, 2021 , Warfvinge et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We are currently focused on identifying which nuclear and/or membrane estrogen receptors (ERα, ERβ, or GPER) are involved in potentiating the effects of 5HT on trigeminal sensory neurons. Previous studies have reported that ERα, ERβ, and GPER are present in trigeminal sensory neurons ( Chen et al, 2021 , Warfvinge et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…The 5HT-potentiated CGRP release occurs after E2 has been interacting in the system for 30–45 min, given our experimental design of a 15 min pretreatment with E2, followed by a 15 min treatment with E2 + 5HT, followed by a 15 min treatment with E2 + 5HT + CAP. Thus, it is also possible that a nuclear estrogen receptor is involved via a rapid signaling mechanism ( Chen et al, 2021 , Marino et al, 2006 ). We are currently focused on identifying which nuclear and/or membrane estrogen receptors (ERα, ERβ, or GPER) are involved in potentiating the effects of 5HT on trigeminal sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These could explain the protective association observed here on CMK pain. Indeed, estrogens are known to influence chronic pain conditions [21]. These combinations of medications and conditions within topics could lead to new CMK pain etiology hypotheses for further exploration.…”
Section: Cmk Pain-related Conditions and Medicationsmentioning
confidence: 99%
“…В свою очередь, для патогенеза МАМ полученные данные могут иметь особое значение: более высокий системный/локальный уровень эстрогена, возможно, обусловливает более выраженное перименструальное его снижение и, таким образом, увеличивает риск провокации приступа ММ [15]. Кроме того, особенности функционирования рецепторов эстрогена, возможно, обусловливают более выраженное снижение болевого порога в период перименструального окна [23,24].…”
Section: Menstrual Cycle and Gynecologic Pathology Characteristics In Mrm And Nmm N (%)unclassified